Gambaran Kecerdasan Emosional Mahasiswa serta Implikasinya dalam Layanan Bimbingan dan Konseling - Fadil Maiseptian (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Students whose emotional intelligence is not well developed will find it difficult to recognize and control their emotions, have low motivation so that they are awkward in getting along and can even lead to aggressive behavior. The purpose of this study is to describe the emotional intelligence students and their implications in guidance and counseling services. The type of research used is descriptive with a quantitative approach. The subjects of this study were students Islamic guidance and counseling (BKI) faculty of dakwah and communication science at UIN Imam Bonjol Padang. Determination of research samples using simple random sampling/ random samples. The instrument used in this study was an emotional intelligence questionnaire. The data analysis technique used is the percentage formula test. The results of the study illustrate that on average the conditions of emotional intelligence of students are in the medium category and need to be improved using the services available in guidance and counseling. So that good emotional intelligence will have an impact on a positive life for every student before entering the adult development stage.